Effects of carvacrol on growth performance, carcass traits, serum biochemistry, and intestinal gut microflora of broiler chickens - Belhadj Slimen, Imen; Val Boa, Mohamadi; Lengliz, Sana; Bejaoui, Bochra; Samti, Hafaoua; Abbassi, Mohamed Salah; M’Hamdi, Naceur; Chaveriat, Ludovic; Martin, Patrick; Abderrabba, Manef; Najar, Taha (Frontiers in Animal Science, 2025)
IntroductionIt has been suggested that reducing the bioenergetic costs of gut inflammation and stimulating the immune system of birds lead to improved growth and feed efficiency in poultry. Essential oils and their chemotypes have been recognized for their antimicrobial properties and emerged as promising molecules that may be used for sustainable poultry production and respond to the challenges posed by the One Health concept.MethodsThis trial was conducted to evaluate the effects of carvacrol at two levels (0 and 20 mg/Kg of diet) on growth performances, carcass traits, serum biochemicals, and intestinal gut microflora counts in broiler chickens. One thousand six hundred 1-day-old broiler chicks were divided equally into 2 groups: CON, the control group, and CARV, the experimental one.ResultsEach group consisted of 08 replicates of 100 chicks each, from 1 to 35 days. Carvacrol supplementation linearly reduced feed intake (P<0.05) and improved the feed conversion ratio (P<0.05). The highest body weight gain (P<0.0001) and daily weight gain (P<0.0001) were recorded in the CARV group. However, the weights of hot and cold carcasses, as well as lymphoid organs were not affected. Similarly, blood biochemistry parameters, except for glucose, and protein electrophoresis fractions were not changed. Carvacrol supplementation modified the immune response by reducing the Albumine/Globuline ratio (P<0.05) and lowering lactic bacteria (P<0.05), Enterobacteriaceae (P<0.0001), and Salmonella (P<0.001) counts in the intestinal gut. Clostridium count wasn’t affected.DiscussionIt can be concluded that carvacrol supplementation enhanced growth performances, decreased intestinal bacterial pathogens, and improved the immune status of broiler chickens. Carvacrol can be consequently recommended as an alternative to antibiotic growth promoters for broilers’ production.